Evaluation of Voltage/Frequency and Voltage Source Inverter Control Strategies for Single-Phase Induction Motors Using MATLAB Simulation - Dakheel, Hashmia S.; Shneen, Salam Waley; Abdullah, Zainab B.; Shuraiji, Ahlam Luaibi (Journal of Robotics and Control (JRC), 2024)
There is a growing interest in studying the single-phase induction motor due to its wide use in many applications, the most important of which are domestic and industrial. A simulation model is built by implementing and running the model using MATLAB to identify the system behavior of the induction motor. To study and analyze the system behavior in different cases, it is proposed to implement and run the model in two ways: the first without control techniques and the second using control techniques. Tests are conducted according to a methodology based on scenarios that include all expected cases that can be assumed to suit real-time operation. To evaluate control strategies, the clear effect between their use and non-use must be demonstrated through clear measurement criteria to include response speed and performance improvement. In induction motor tests, the focus is on electrical and mechanical quantities and the transient and steady state of the system, including a 220-volt supply voltage and a 50 Hz frequency. The initial test case refers to using the model to simulate three cases: the first without load, the second with a constant load of one newton meter, and the third operating the motor as a pump by changing the load according to the pumping quantity and linked to the motor output. After conducting these tests, the different simulation results can be indicated in terms of the change in electrical and mechanical quantities over time during the proposed operating period. The results showed the high starting current that may affect the motor, and the response time for the motor to operate at the rated speed can be considered. Therefore, this requires the use of techniques to improve performance and provide response speed with a gradual increase in the starting current to protect the motor from high starting current. Voltage and frequency control techniques, as well as voltage-to-frequency ratio and another technique representing the voltage source inverter, were used. The results indicate a clear improvement through the stability of the motor by operating with a short response time compared to other cases and the specified rotational speed and specified torque, which shows a relatively high-efficiency performance.